2022
DOI: 10.1039/d2tb01819e
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid@MOF-74 as a host–guest system with antimicrobial activity

Abstract: Linezolid (LNZ) is a new-generation synthetic molecule for the antibacterial treatment of severe infections, particularly in infective cases where the bacterial resistance to first-choice drugs is caused by gram-positive pathogens....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Also in recent years, the combination of antibacterial agents or drugs housed in copper-based MOFs have been reported as drug delivery systems due to their favorable biodegradation characteristics in the presence of biological fluids. 112,113 The objective of this combination is to generate multiple mechanisms of antimicrobial action. 95 In 2022, Ramos et al 112 proposed a MOF-74(Cu) system with housed linezolid, and the system effect reported a statistically significant decrease in the minimum inhibitory concentration (MIC) reported for this drug, for which only 0.112 mg of linezolid was required for total inhibition of S. aureus.…”
Section: Copper-based Mofs As Antimicrobial Materials and Hosting Oth...mentioning
confidence: 99%
See 1 more Smart Citation
“…Also in recent years, the combination of antibacterial agents or drugs housed in copper-based MOFs have been reported as drug delivery systems due to their favorable biodegradation characteristics in the presence of biological fluids. 112,113 The objective of this combination is to generate multiple mechanisms of antimicrobial action. 95 In 2022, Ramos et al 112 proposed a MOF-74(Cu) system with housed linezolid, and the system effect reported a statistically significant decrease in the minimum inhibitory concentration (MIC) reported for this drug, for which only 0.112 mg of linezolid was required for total inhibition of S. aureus.…”
Section: Copper-based Mofs As Antimicrobial Materials and Hosting Oth...mentioning
confidence: 99%
“…112,113 The objective of this combination is to generate multiple mechanisms of antimicrobial action. 95 In 2022, Ramos et al 112 proposed a MOF-74(Cu) system with housed linezolid, and the system effect reported a statistically significant decrease in the minimum inhibitory concentration (MIC) reported for this drug, for which only 0.112 mg of linezolid was required for total inhibition of S. aureus. In addition, it was reported that MOF-74(Cu) as a study control also causes an inhibition effect on the growth of this bacterial strain; however, Liu in the same year, proposed this same MOF-74 but bimetallic (Mg-Cu), which shows excellent results of the evaluated antibacterial activity.…”
Section: Copper-based Mofs As Antimicrobial Materials and Hosting Oth...mentioning
confidence: 99%
“…29,30 Such apparent disadvantage has been recently explored in potential clinical applications, since the degradation of MOF-74(Mg), under physiological conditions, gradually released Mg(II) metal centers. 31,32 MOF-74 (DOT) ligand was also reported as a non-toxic compound. 33 This work inspired us to investigate the gradual decomposition of MOF-74(Cu) under a physiological environment.…”
Section: Introductionmentioning
confidence: 99%